2021
DOI: 10.1002/slct.202100358
|View full text |Cite
|
Sign up to set email alerts
|

Characterization Study of Cytotoxicity of Green Synthesized ZnO Nanoparticles Loaded with Anti‐Cancer Doxorubicin Drug

Abstract: The green synthesized zinc oxide nanoparticle (ZnO) was filled with a commercially available anti-cancer drug, Doxorubicin (DoX). The loading of the drug into ZnO was validated using UV-Visible and Raman spectroscopy. X-ray diffraction data showed the wurtzite structure of the nanoparticles of ZnO. Scanning electron microphotography images detected the encapsulation of DoX drugs into ZnO nanoparticles. Fourier transformer infrared spectrum of DoX loaded ZnO showed a single band at 478 cm À 1 attributed to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…The results suggest that the A. niger mediated ZnO NPs can effectively suppress the growth of studied cancer cell. Similar ndings have been reported by Padalia and Chanda [43] and Gomathi et al [44], whereby the capability of green ZnO-NPs to destroy cancer cells has been demonstrated. Furthermore, ZnO-NPs have been observed to disintegrate within the lysosome and donate Zn 2+ ions [45].…”
Section: Cytotoxicity Assay Of Zno Nps Using (Mtt) Assay Protocolsupporting
confidence: 90%
“…The results suggest that the A. niger mediated ZnO NPs can effectively suppress the growth of studied cancer cell. Similar ndings have been reported by Padalia and Chanda [43] and Gomathi et al [44], whereby the capability of green ZnO-NPs to destroy cancer cells has been demonstrated. Furthermore, ZnO-NPs have been observed to disintegrate within the lysosome and donate Zn 2+ ions [45].…”
Section: Cytotoxicity Assay Of Zno Nps Using (Mtt) Assay Protocolsupporting
confidence: 90%
“…Phytochemicals such as alcohols, phenols, amines, carboxylic acids, and others present in plant extracts have the capability to interact with the surfaces of zinc and iron, thereby aiding in the stabilization of nanoparticles. The broad peak within the 3400-3300 cm −1 range, a common occurrence in FTIR spectra, provides confirmation of the existence of intermolecular hydrogen bonding [24]. The absorption peaks at approximately ~1570 and ~1400 cm -1 in both spectra, known to come from plant extracts and help particle synthesis, are assigned to C=C stretching and C-C stretching vibrations, respectively.…”
Section: Ft-ir Resultsmentioning
confidence: 57%
“…Zinc oxide-DOX cells were 99.4% inhibited at a dosage of 100 g/mL. Thus, the findings offer convincing support for green biosynthesized ZnO, which may work well as a potential nano-drug carrier for the targeted drug delivery system [96].…”
Section: Using Zinc Oxide Nanoparticles As a Cancer Drug Deliverymentioning
confidence: 52%